Pyramidal, rodlike, spherical gold nanostructures for direct electron transfer of copper, zinc-superoxide dismutase application to superoxide anion biosensors - Liu, Haiqing (Langmuir : the ACS journal of surfaces and colloids, 2008)
It is the first time that direct electron transfer of copper, zinc-superoxide dismutase (Cu, Zn-SOD) is realized at nanospherical, nanorodlike, and nanopyramidal gold nanostructures, without any mediators or promoters. Thermodynamic and kinetic parameters of the electron transfer vary with the morphology of the electrodeposited gold nanostructures, suggesting the morphology-dependent electrochemistry of SOD. Experimental results reveal that SOD is strongly confined onto the nanostructured gold surfaces and processes its inherent enzymatic activity after being adsorbed on all three kinds of gold nanostructures, which also enable the direct electron transfer of SOD itself. A combination of the facilitated direct electron transfer and the bifunctional enzymatic catalytic activities of the SOD substantially offers a dual electrochemical approach to determination of O2(*-), in which O2(*-) could be detected both anodically and cathodically. In both the oxidation and reduction regions, the present O2(*-) biosensors display excellent analytical performance, such as wide linear range, low detection limit, quick response time, and good stability and reproducibility, while not being limited by interferences, for instance, uric acid, ascorbic acid, and hydrogen peroxide